Optimizing the transient transfection process of HEK-293 suspension cells for protein production by nucleotide ratio monitoring - Bassani Molinas, María (2014)
Fil: Bassani Molinas, María de los Milagros. ANLIS Dr.C.G.Malbrán. Unidad Operativa Centro de Contención Biológica; Argentina.